Atypical White Matter Connectivity in Dyslexic Readers of a Fairly Transparent Orthography - Žarić, Gojko; Timmers, Inge; Gerretsen, Patty; Fraga González, Gorka; Tijms, Jurgen; van der Molen, Maurits W.; Blomert, Leo; Bonte, Milene (Frontiers in Psychology, 2018)
Atypical structural properties of the brain’s white matter bundles have been associated with failing reading acquisition in developmental dyslexia. Because these white matter properties may show dynamic changes with age and orthographic depth, we examined fractional anisotropy (FA) along 16 white matter tracts in 8-11 year old dyslexic (DR) and typically reading (TR) children learning to read in a fairly transparent orthography (Dutch). Our results showed higher FA values in the bilateral anterior thalamic radiations of DRs and FA values of these tracts scaled with behavioral reading related scores. Furthermore, DRs tended to have atypical FA values in the bilateral arcuate fasciculi. Children’s age additionally predicted FA values along the tracts. Together, our findings suggest differential contributions of cortical and thalamo-cortical pathways to the developing reading network in dyslexic and typical readers, possibly indicating prolonged letter by letter reading or increased attentional and/or working memory demands in dyslexic children during reading.